ANALISIS KUALITAS LAYANAN WEBSITE BANK BTPN PALEMBANG MENGGUNAKAN METODE WEBQUAL 4.0 - Difa Chairunnisa; Tata Sutabri (ADISAM PUBLISHER, 2023)
Bank BTPN is a national private bank that focuses on empowering communities by providing access to financial services to underserved sectors. Bank BTPN has been operating in Palembang for several years and continues to develop innovative and inclusive financial services for the local community. This journal discusses the history, profile, and services provided by Bank BTPN in Palembang. The research method used is literature study and observation. The results show that Bank BTPN has successfully made a significant contribution to improving financial inclusion and economic empowerment in Palembang. Bank BTPN has a strong strategy in building relationships with customers and the community through financial education programs and financial services that meet their needs. However, the challenge faced by Bank BTPN in Palembang is competition with other banks that also ofler similar financial services. Therefore, Bank BTPN needs to continue to strengthen its marketing strategy and product innovation to maintain its position as a bank that is able to provide inclusive and aflordable financial services to the community in Palembang